PENDAMPINGAN LITERASI DAN NUMERASI SISWA SEKOLAH DASAR MELALUI CERITA ANAK DIGITAL BERBASIS FLIPBOOK DALAM PROGRAM BELAJAR KREATIF BERKELANJUTAN - Aliera Azzahra Putri; Anastya Basyith Ad Dauwi; Sabrina Putri Salsabila; Yunauro Prespi Mubaroq; Fauzan Dwi Alfianto; Decenni Amelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Literacy and numeracy are fundamental skills that must be developed from the elementary school level because they form the basis for students’ thinking abilities and academic success. However, learning activities in the community are still often limited to conventional methods that are less engaging for children. This study aims to describe the implementation of literacy and numeracy assistance for elementary school students through digital children’s stories based on flipbooks within the Sustainable Creative Learning Program. This research used a descriptive qualitative approach. Data were collected through observation, interviews, documentation, and student questionnaires during the implementation of the program. The assistance activities were carried out during a one-month community service program (KKN) in Harapan Jaya, Bekasi, through several thematic activities that integrated reading and numeracy exercises using digital flipbooks. The results show that the use of digital flipbook-based children’s stories made students more interested, active, and motivated in learning. Students were able to better understand reading content and apply simple numeracy concepts through contextual and enjoyable activities. Overall, digital flipbook media played an important role in supporting literacy and numeracy assistance by creating a more meaningful, interactive, and student-centered learning experience.